Fat Augmentation as Adjunct to CORE Facelift Surgery - Wever, Capi C. (Facial Plastic Surgery, 2021)
Ruling out cases with strong jawlines, well-developed mid-cheek regions, and good fat presence, if done artistically, fat augmentation strongly assists midface definition and can replenish hollowed regions of the face. This is particularly true for candidates with low bodyfat or smaller skull structures. Hence, fat grafting is a strong adjunct to conventional excisional techniques in facial rejuvenation surgery, regardless of experience, technique, or geographical embedding. While CORE facelift techniques remain the golden standard that define the top level of facelift surgery, fat augmentation has its unique place along the full stretch of an individual surgeon's learning scope, as it will potentially improve results regardless of where one stands.
Keywords: facelift; lipofilling; fat transfer; surgery